When Your Boss Is Under Pressure: On the Relationships Between Leadership Inconsistency, Leader and Follower Strain - Klebe, Laura; Klug, Katharina; Felfe, Jörg (Frontiers in Psychology, 2022)
It is widely acknowledged that leadership is crucial for follower health. Under stress, positive leader behaviors such as transformational leadership may decrease and the risk of negative behaviors such as abusive leadership may increase. Followers experience these discrepancies in leadership between routine and stressful periods as inconsistent. While positive and negative leadership is generally associated with follower strain, inconsistency may be stressful by itself, because it entails insecurity and unpredictability in the leader-follower relationship. We suggest that the level of perceived inconsistency and volatility in leaders’ behavior across situations is an additional risk factor for follower health. Moreover, we expect perceived inconsistency to be stronger when leaders are strained. This survey study with N = 304 employees examines the relationships between leadership inconsistency and leader as well as follower strain from a followers’ perspective. Participants rated their leaders’ transformational and abusive leadership separately for routine and stressful conditions, their leaders’ strain and their own strain. Employees who experienced stronger discrepancies in leadership between routine and stressful conditions, i.e. more inconsistency, experienced more strain. Moreover, from a followers’ perspective, inconsistencies were stronger when leaders were strained. The findings provide evidence that leadership is less stable and consistent than generally assumed and that inconsistency is an additional risk factor. Leader strain may threaten the consistency of leadership and thereby negatively affect follower health.